2013
DOI: 10.1158/1541-7786.mcr-12-0572
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-CaMKII Plays a Critical Role in Determining the Aggressive Behavior of Human Osteosarcoma

Abstract: Osteosarcoma is among the most frequently occurring primary bone tumors, primarily affecting adolescents and young adults. Despite improvements in osteosarcoma treatment, more specific molecular targets are needed as potential therapeutic options. One target of interest is alpha-Ca2+/calmodulin-dependent protein kinase II (α-CaMKII), a ubiquitous mediator of Ca2+-linked signaling, which has been shown to regulate tumor cell proliferation and differentiation. Here, we investigate the role of α-CaMKII in the gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…As we and others have previously shown111622, overexpression of WT CaMKII significantly increases cell proliferation, when compared to EV control cells, as measured by Cell Titer Blue (Fig. 3A,B) and clonogenic assays (Fig.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…As we and others have previously shown111622, overexpression of WT CaMKII significantly increases cell proliferation, when compared to EV control cells, as measured by Cell Titer Blue (Fig. 3A,B) and clonogenic assays (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Recent studies have demonstrated that CaMKII is involved in controlling osteosarcoma and gastric cancer cell invasion and migration1622, and lung cancer tumourigenicity29, and we have previously implicated CaMKII in breast cancer cell proliferation1130. However, the role of CaMKII phosphorylation in cancer cell invasion and migration has not previously been explored.…”
Section: Discussionmentioning
confidence: 98%
“…The role for the different isoforms of CaM Kinases in oncogenesis is rapidly emerging and evidence supports the involvement for CaM KK, CaM KI, CaM KIV, CaM KII as well as their various substrates and cellular targets in cancer development [60,[68][69][70][71][72][73][74]. Consistent with our data, Iglewski et al demonstrated that urotensin treatment of primary smooth muscle cells activated a CaM KK/CaM KI/ERK proliferation pathway although the ability of other hormones to inhibit this process was not examined [75].…”
Section: Discussionsupporting
confidence: 88%
“…Overexpression of a-CaMKII in several osteosarcoma cell lines results in an increase in migration, proliferation, and a dramatic increase in invasion, all hallmarks of EMT, while knockdown results in a significant reduction in these behaviors. 83 CaMKID, a homolog of CaMKII, is overexpressed in invasive carcinomas and leads to EMT, increased cell proliferation, loss of cellcell adhesions, and increases migration and invasion. 84 In prostate cancer cells, the non-canonical Wnt5a calcium pathway was shown to be important in wound closure and cell migration; inhibition of CaMKII with AIP prevents wound closure in scratched confluent sheets and decreases cell motility in the same cell lines.…”
Section: Molecular Regulation Of Epithelial Scattering By Calcium/calmentioning
confidence: 99%